Selection and cultivation of seaweed Kappaphycus alvarezii using a long line system (outdoor) - Gloria I. Satriani; Dinar Tri Soelistyowati; Alimuddin Alimuddin; Harton Arfah; Irzal Effendi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
In outdoor cultivation at Amal Beach, three seeding mass selections were reared for 30 days for each cycle. Each variety had a different DGR %/day (Daily Growth Rate %/day) value at the end of the growing season on G1-G2-G3 ranging from 3.62-5.90 %/day, which were still categorized as good, and G3 var.Lampung had the highest DGR value. Carrageenan yield values in this study, G1 to G3, ranged from 23.16% to 45.87%, where the G3 G2 G1 treatment. The best thallus samples (20% were selected for each generation) resulted in carrageenan yield sample population in each variety, where var.Lampung var.Tarakan var.Kupang. The biplot analysis shows that the DGR variable vector coincides with the IAA, Phosphate, Gibberellin, and Ammonia vectors. Ammonia stepwise regression analysis (sig) affects DGR with an Ammonia coefficient value of 4.89; meaning that for each increase in the Ammonia value by one unit, the estimated mean value of DGR will increase by 4.89. Thus, the application of themassbased on the results of this study was able to increase the DGR valueKappaphycus alvarezii,which in turn produce the highest yield of carrageenan withK. alvareziivar.Lampung G3 was the best seed candidate to be developed at the seaweed cultivation site in Tarakan City.Keywords:AlgaePhytohormonesCarrageenanNitrogenViscosity